Agroclimatic Indices of Rice (Oryza sativa L.) Influenced by Different Planting Times - Sultana, A; Shaikh, NY; Zahan, MS; Akter, R; Islam, SA; Issak, M (Bangladesh Rice Journal, 2020)
Meteorological variables have an important role in rice production. Considering this study was carried out in Aman season of 2016 at the research field of Bangladesh Rice Research Institute, Gazipur. The research was conducted in order to investigate the effects of planting time on various agrometeorological indices viz., accumulated growing degree days (GDD), heliothermal units (HTU), photo thermal units (PTU), and heat use efficiency (HUE) the yield of advanced/variety grown under different time of transplanting in the Gazipur climatic zone (AEZ, 28). The research was conducted as a split plot using randomized complete block design (RCBD) with three replications. In this research, three planting times (1st Aug, 16th Aug, and 31th Aug) and the Advanced lines/varieties BR (Bio) 9786-BC2-119-1-1, BR (Bio) 9786-BC2-132-1-3 and BRRI dhan49 (check variety) were used in the experiment. The results showed that planting time significantly affected on grain yield. Among the genotypes, BR (Bio) 9786-BC2-119-1-1 and BR (Bio) 9786-BC2-132-1-3 produced significantly higher grain yield than check variety BRRI dhan49 in all the planting times. The variety (BRRI dhan49), transplanted at the first August, took maximum calendar days (136 days) to attain different phenological stages till physiological maturity coupled with highest growing degree days (2420 degree day) for maturity, lowest heat use efficiency (2.25 kg ha-1 c-1 day-1), highest heliothermal units (15141.01 degree day hours) and lowest photothermal units (29678.81 degree day hours) resulting lower yield. Among the advanced lines the line BR (Bio) 9786-BC2-119-1-1 took higher calendar day (134 days) to attain different phenological stages till physiological maturity coupled with higher growing degree days (2393 degree day) for maturity, heat use efficiency (2.76 kg ha-1 c-1 day-1), heliothermal units (13759.75 degree day hours) and photothermal units (30112.51 degree day hours) resulting higher yield. Taken together, the results indicate that the advanced line, BR (Bio) 9786-BC2-119-1-1, could be select as a best advanced line to release as a variety due to its higher grain yield. Bangladesh Rice j. 2019, 23(2): 87-94